Porphyrin Excretion Resulting From Mutation of a Gene Encoding a Class I Fructose 1,6-Bisphosphate Aldolase in Rhodobacter capsulatus - Ding, Hao; Saer, Rafael G.; Beatty, J. Thomas (Frontiers in Microbiology, 2019)
This paper describes a mutant (called SB1707) of the Rhodobacter capsulatus wild type strain SB1003 in which a transposon-disrupted rcc01707 gene resulted in a ~25-fold increase in the accumulation of coproporphyrin III in the medium of phototrophic (anaerobic) cultures grown in a yeast extract/peptone medium. There was little or no stimulation of pigment accumulation in aerobic cultures. Therefore, this effect of rcc01707 mutation appears to be specific for the anaerobic coproporphyrinogen III oxidase HemN as opposed to the aerobic enzyme HemF. The protein encoded by rcc01707 is homologous to Class I fructose 1,6-bisphosphate aldolases, which catalyze a glycolytic reaction that converts fructose 1, 6-bisphosphate to dihydroxyacetone phosphate and glyceraldehyde 3-phosphate, precursors of pyruvate. There were significant differences in coproporphyrin III accumulation using defined media with individual organic acids and sugars as the sole carbon source: pyruvate, succinate and glutamate stimulated accumulation the most, whereas glucose suppressed coproporphyrin III accumulation to 10% of that of succinate. However, although quantitatively lesser, similar effects of carbon source on the amount of accumulated pigment in the culture medium were seen in a wild type control. Therefore, this mutation appears to exaggerate effects also seen in the wild type strain. It is possible that mutation of rcc01707 causes a metabolic bottleneck or imbalance that was not rectified during growth on the several carbon sources tested. However, we speculate that, analogous to other fructose 1,6-bisphosphate aldolases, the rcc01707 gene product has a "moonlighting" activity that in this case is needed for the maximal expression of the hemN gene. Indeed, it was found that the rcc01707 gene is needed for maximal expression of a hemN promoter-lacZ reporter. With the decrease in hemN expression due to the absence of the rcc01707 gene product, coproporphyrinogen III accumulates and is released from the cell, yielding the spontaneous oxidation product coproporphyrin III.